A new record of the genus Yua (Vitaceae) from Vietnam - Dang, Viet Cuong; Lu, Limin; Nguyen, van Hieu; Habib, Sadaf; Barrett, Russell L.; Chen, Zhiduan (Phytotaxa, 2016)
Yua C.L. Li (Vitaceae), a genus previously known from China, Nepal and India, is newly recorded from Vietnam. A specimen discovered in the rainforest of Lao Cai province, northern Vietnam was identified as Yua austro-orientalis (F.P. Metcalf) C.L. Li based on both morphological and molecular data. To improve our understanding of relationships between Yua and Parthenocissus Planch., we present diagnostic characteristics for these two genera. We discuss leaf, stem and seed features used to distinguish between Y. austro-orientalis and Y. thomsonii (M.A. Lawson) C.L. Li, a species widely distributed in China, Nepal and northern India. The opportunity is taken to review the typification of all Yua taxa. A lectotype is selected for Vitis thomsonii M.A. Lawson.